Estado nutricional y hábitos alimentarios post confinamiento por COVID-19 en adultos mayores de la parroquia Imantag, Cotacachi, 2022: Nutritional status and eating habits post confinement by COVID-19 in older adults from the Imantag parish, Cotacachi, 2022 (La U Investiga, 2024)
During confinement by COVID-19, significant changes in the eating habits were observed, characterized by an unhealthy eating pattern, increased intake of ultra-processed products of low nutritional quality, triggering a higher risk of malnutrition. The objective of the present study was to relate the post-COVID-19 confinement nutritional status and eating habits of older adults in the Imantag parish. This is descriptive, comparative because measurements of eating habits were made before and after confinement. The nutritional status was evaluated through the BMI of 57 AM, taking anthropometric measurements, in addition, the food quality survey (ECAAM) was applied. It was identified that 70.2% of the sample belong to the female sex. The means and standard deviations of the variables age, weight, height, and BMI were 76.3 ± 6.46 years; 49.5 ± 8.12kg; 1.45±0.07m; 23.7 ± 4.09 kg/m2, respectively; resulting in 66.7% of the population having a normal nutritional status. The quality of food before confinement in 80.7% of the population was poor and after confinement, 71.9% of older adults continued with a similar evaluation obtaining a slight improvement. A p-value =0.017, less than 0.05, was determined using the Student's t-statistic for paired samples, indicating there are significant changes in the quality of food after confinement. There is no statistically significant relationship between nutritional status and eating habits.